Sintesis Biodiesel Menggunakan Katalis Campuran Calcium Hydroxide dan Calcite - Horasdia Saragih (Department of Physics, Sebelas Maret University, 2021)
Fatty acid methyl esters (FAME, biodiesel) have been synthesized using a mixture of calcium hydroxide [Ca(OH)2] and calcite [CaCO3] catalyst. The fabrication was carried out by transesterifying triglycerides from palm oil using methanol at temperature of 60oC. The mixture of calcium hydroxide [Ca(OH)2] and calcite [CaCO3] catalyst was synthesized from CaO by exposed CaO to the air at room temperature. Various transesterification times have been involved in transesterification process. Based on the results obtained, it was found that the mixture of Ca(OH)2 and CaCO3 has catalytic characteristics, so that it can transesterify triglycerides and produce the FAME. There are 10 types of FAME produced from the palm oil triglycerides in this transesterification. Five of this types were saturated FAME and others were unsaturated FAME. The highest concentration of FAME is cis-9-octadecenoic acid methyl ester. The longer transesterification process, the more FAME is produced. Referring to the results of this study, it shows that the mixture of Ca(OH)2 and CaCO3 has the potential to be used as a catalyst for synthesizing biodiesel in the future.